Impact of dual-baculovirus infection on the Sf9 insect cell transcriptome during rAAV production using single-cell RNA-seq - Virgolini, Nikolaus (2023)
Funding Information: The authors gratefully acknowledge the funding from the European Union's Horizon 2020 research and innovation program under the Marie Sklodowska‐Curie grant agreement no. 813453 and from Fundação para a Ciência e a Tecnologia/Ministério da Ciência, Tecnologia e Ensino Superior (FCT/MCTES, Portugal) through national funds to iNOVA4Health (UIDB/04462/2020 and UIDP/04462/2020) and the Associate Laboratory LS4FUTURE (LA/P/0087/2020). The authors would also like to thank Généthon for kindly providing the rBAC‐GFP baculovirus, Marcos Sousa (iBET) for his support in running the bioreactors, and Siobhan Cashman and Helen Smith (both BD Biosciences) for their support on the Rhapsody platform. The graphical abstract and Figure 1a were created with BioRender.com . Funding Information: The authors gratefully acknowledge the funding from the European Union's Horizon 2020 research and innovation program under the Marie Sklodowska-Curie grant agreement no. 813453 and from Fundação para a Ciência e a Tecnologia/Ministério da Ciência, Tecnologia e Ensino Superior (FCT/MCTES, Portugal) through national funds to iNOVA4Health (UIDB/04462/2020 and UIDP/04462/2020) and the Associate Laboratory LS4FUTURE (LA/P/0087/2020). The authors would also like to thank Généthon for kindly providing the rBAC-GFP baculovirus, Marcos Sousa (iBET) for his support in running the bioreactors, and Siobhan Cashman and Helen Smith (both BD Biosciences) for their support on the Rhapsody platform. The graphical abstract and Figure 1a were created with BioRender.com. Publisher Copyright: © 2023 iBET - Instituto de Biologia Experimental e Tecnologica and The National Institute for Bioprocessing Research and Training. Biotechnology and Bioengineering published by Wiley Periodicals LLC.